Adrian Goldstone and Nelson Valjean. - Maurice Dunbar:::Creator::::::::::::; Hayman, Lee Richard (collector):::Contributor::::::::::::
Adrian Goldstone (prominent collector of Steinbeck books) and Nelson Valjean (author of John Steinbeck, the Errant Knight biography). Valjean is signing a copy of his book.